2007
DOI: 10.1002/ejoc.200700263
|View full text |Cite
|
Sign up to set email alerts
|

Eight‐Membered‐Ring Lactams – New Scaffolds for Combinatorial Chemistry Prepared by Ring‐Expansion of 1,4‐Diketones with Primary Amines

Abstract: Eight-membered-ring lactams were prepared by the Bi-catalyzed reaction of 1,4-diketones with primary amines. These lactams define a new type of non-planar molecular scaffold with three points allowing for diversification, which were evaluated as the basis for combinatorial library synthesis. For this reason, reaction conditions were optimized, and the scope and limitations were investigated. After the Bi-catalyzed reaction, further diversification was achieved by ester

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…To elucidate the scope of this re-action regarding the amine, we attempted to convert BnNH 2 , EtOCH 2 CH 2 NH 2 , iPrNH 2 , CyNH 2 , GlyOtBu, and β-AlaOtBu, [19] but only in the case of BnNH 2 was a product, 6c, obtained in low yield and low purity (Scheme 4, Table 1). Although we were convinced from our earlier work that the Bi-salt is required for the reaction, [11][12][13] when we attempted to convert ethyl ester 5b with MeNH 2 without Bi-additive, the product 6b was indeed formed. Again, several reaction parameters were screened, and it was found that conversion with two equivalents of amine at 100°C for 16 h gave optimal results, although the yield was still moderate (38 %).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To elucidate the scope of this re-action regarding the amine, we attempted to convert BnNH 2 , EtOCH 2 CH 2 NH 2 , iPrNH 2 , CyNH 2 , GlyOtBu, and β-AlaOtBu, [19] but only in the case of BnNH 2 was a product, 6c, obtained in low yield and low purity (Scheme 4, Table 1). Although we were convinced from our earlier work that the Bi-salt is required for the reaction, [11][12][13] when we attempted to convert ethyl ester 5b with MeNH 2 without Bi-additive, the product 6b was indeed formed. Again, several reaction parameters were screened, and it was found that conversion with two equivalents of amine at 100°C for 16 h gave optimal results, although the yield was still moderate (38 %).…”
Section: Resultsmentioning
confidence: 89%
“…[12] We have furthermore applied this reaction for the conversion of tetrahydrofuran, tetrahydrothiophene, and pyrrolidine derivatives to yield oxazocanes 2b, thiazocanes 2c, and diazocanes 2d. [13] From a mechanistic point of view, the ring-enlargement seems to proceed via an azabicyclo [3.3.0]octane intermediate 3, which was proved in one case by isolation and crystallographic characterization of an example with R = H and X = CH 2 as the imine-tautomer.…”
Section: Introductionmentioning
confidence: 99%
“…After ring expansion, the ester moieties were saponified and amidated with another set of primary amines R C -NH 2 to give products 4. [2] A mechanistic rationale for the ring expanding transformation considers nucleophilic attack of the amine to both carbonyl groups of the 1,4-diketone moiety with formation of the bicyclic intermediate 3, as proposed for the Paal-Knorr pyrrole synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Initial optimization of this transformation was carried out with the tetrahydrothiophene derivative 5 and Bn-NH 2 (Table 1, entry 1, product 8a). The reaction conditions given in Scheme 4 were adopted for all four amines R-NH 2 (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The interconversion of the five-membered ring in starting materials 1 to an eight-membered ring in products 2 is assumed to proceed through intermediate 3 with a bicyclo [3.3.0] skeleton. [2] Furthermore, we have been able to convert tetrahydrothiophenes 1 (X = S) and pyrrolidines (X = N-PG) to respective thiazocinones 4 (X = S) [3] and diazocinones (X = N-R D ), [4] the latter having a fourth point of diversity R D , which was introduced after deprotection of secondary amine N-PG. [2] Furthermore, we have been able to convert tetrahydrothiophenes 1 (X = S) and pyrrolidines (X = N-PG) to respective thiazocinones 4 (X = S) [3] and diazocinones (X = N-R D ), [4] the latter having a fourth point of diversity R D , which was introduced after deprotection of secondary amine N-PG.…”
Section: Introductionmentioning
confidence: 99%